The Etiology of Pneumonia in HIV-1-infected South African Children in the Era of Antiretroviral Treatment: Findings From the Pneumonia Etiology Research for Child Health (PERCH) Study. (September 2021) - Moore, David P.; Baillie, Vicky L.; Mudau, Azwifarwi; Wadula, Jeannette; Adams, Tanja; Mangera, Shafeeka; Verwey, Charl; Sipambo, Nosisa; Liberty, Afaaf; Prosperi, Christine; Higdon, Melissa M.; Haddix, Meredith; et al.
Abstract : Background: HIV-1 infection predisposes to an increased burden of pneumonia caused by community-acquired and opportunistic pathogens. Methods: Within the context of the Pneumonia Etiology Research for Child Health case-control study of under 5 pneumonia, we investigated the etiology of World Health Organization-defined severe/very severe pneumonia requiring hospitalization in South African HIV-infected children. Nasopharyngeal-oropharyngeal swabs and blood, collected from cases and age- and season-matched HIV-infected controls attending outpatient antiretroviral therapy (ART) clinics, were analyzed using molecular diagnostic methods. Cases were also investigated for tuberculosis. Etiologic fractions among cases with radiologically confirmed pneumonia were derived using Bayesian analytic techniques. Results: Of 115 HIV-infected cases, 89 (77.4%) had radiologically confirmed pneumonia. Severe immunosuppression (adjusted odds ratio, 32.60; 95% confidence interval, 7.25–146.64) was significantly associated with radiologically confirmed pneumonia. Cotrimoxazole prophylaxis (46.4% vs. 77.4%) and ART (28.2% vs. 83.1%) coverage were significantly lower in cases compared with ART-clinic controls. An etiologic agent was identified in 99.0% of the radiologically confirmed cases. The 'top 4' pathogens associated with radiologically confirmed pneumonia were Pneumocystis jirovecii [23.0%; 95% credible interval (CrI), 12.4%–31.5%], Staphylococcus aureus (10.6%; 95% CrI, 2.2%–20.2%), pneumococcus (9.5%; 95% CrI, 2.2%–18.0%) and respiratory syncytial virus (9.3%; 95% CrI, 2.2%–14.6%). Bacteremia (6.7%) and in-hospital death (10.1%) were frequent among those with radiologically confirmed disease. Conclusions: Pneumocystis jirovecii, S. aureus, pneumococcus and respiratory syncytial virus contribute a considerable burden of radiologically confirmed pneumonia in South African HIV-infected children under 5 years. Expediting access to ART and cotrimoxazole prophylaxis would decrease the burden of pneumonia in these children. Abstract : Supplemental Digital Content is available in the text.